Significant and meaningful effects in sports biomechanics research - Knudson, D. (Sports Biomechanics, 2009)
Errors in statistical analysis of multiple dependent variables and in documenting the size of effects are common in the scientific and biomechanical literature. In this paper, I review these errors and several solutions that can improve the validity of sports biomechanics research reports. Studies examining multiple dependent variables should either control for the inflation of Type I errors (e.g. Holm's procedure) during multiple comparisons or use multivariate analysis of variance to focus on the structure and interaction of the dependent variables. When statistically significant differences are observed, research reports should provide confidence limits or effect sizes to document the size of the effects. Authors of sports biomechanics research reports are encouraged to analyse and present their data accounting for the experiment-wise Type I error rate, as well as reporting data documenting the size or practical significance of effects reaching their standard of statistical significance.